Un caso teratológico de fasciación en Agave inaequidens C. Koch (Amaryllidaceae) en la cuenca de Pátzcuaro, Michoacán (México) - Madrigal-Sanchez, Xavier; Diaz-Barriga, Horalia (Instituto de Ecología, A.C., 1991)
A teratological phenomenon known as fasciation is described from an individual of the wild species Agave inaequidens C.  Koch, growing in the Patzcuaro Basin, State of Michoacan  (México). The habitat corresponds to strongly disturbed pine-oak forest, with a total annual rainfall of ^1 000 mm, 16 °C of mean annual temperature, and soils of Andosol type and  andesitic bedrock.The most striking morphological character is the widening of  the scape, wich is fíat, reaches 1.4 m at the middle, even though  it has a normal height of 4.25 m.